2014
DOI: 10.1002/ejoc.201402909
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Chemoselective Formation of Spiroindolinone–Isoindolinone by a Palladium‐Catalyzed Buchwald–Hartwig Addition–Elimination Sequence

Abstract: The usual way to synthesize spiroindolinones is the application of isatin derivatives. Here, we report the first Pd‐catalyzed Buchwald–Hartwig addition–elimination strategy for the formation of the spiroindolinone–isoindolinone architecture. The application of the Ugi‐4‐component reaction (Ugi‐4CR) allows the facile introduction of diversity and increases the practicality of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…From Ugi precursor 378 featuring a tertiary benzamide group, spiroindolinone–isoindolinones were formed in moderate to excellent yield (27–98%) through sequential amide coupling/addition–elimination steps via intermediate 379 . 316 Likewise, alkyne-containing Ugi adduct 380 was transformed into spiropyrrolidone–indolines (30–97% yield) by domino amide N-arylation and Michael addition reactions involving intermediate 381 . 317 These methods represent an ideal alternative to traditional isatin functionalization protocols to obtain spiroxindoles 318 due to the simplicity of the reaction setup and the broader scope offered.…”
Section: Amides and Amide Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…From Ugi precursor 378 featuring a tertiary benzamide group, spiroindolinone–isoindolinones were formed in moderate to excellent yield (27–98%) through sequential amide coupling/addition–elimination steps via intermediate 379 . 316 Likewise, alkyne-containing Ugi adduct 380 was transformed into spiropyrrolidone–indolines (30–97% yield) by domino amide N-arylation and Michael addition reactions involving intermediate 381 . 317 These methods represent an ideal alternative to traditional isatin functionalization protocols to obtain spiroxindoles 318 due to the simplicity of the reaction setup and the broader scope offered.…”
Section: Amides and Amide Derivativesmentioning
confidence: 99%
“…Van der Eycken and co-workers published a related post-Ugi functionalization to construct complex spiroindolinones from analogous intermediates (Scheme ). From Ugi precursor 378 featuring a tertiary benzamide group, spiroindolinone–isoindolinones were formed in moderate to excellent yield (27–98%) through sequential amide coupling/addition–elimination steps via intermediate 379 . Likewise, alkyne-containing Ugi adduct 380 was transformed into spiropyrrolidone–indolines (30–97% yield) by domino amide N-arylation and Michael addition reactions involving intermediate 381 .…”
Section: Amides and Amide Derivativesmentioning
confidence: 99%
“…These results clearly indicated that the formation of CÀ C bond is through a copper catalyzed coupling process rather than the S N Ar pathway as proposed in Van der Eycken's work. [12] On the basis of previous copper catalysed coupling reaction investigations [14] and our control experiments, a plausible mechanism for this tandem CÀ N/CÀ C coupling process is proposed in Scheme 8. The oxidative addition of copper catalyst to A which was generated from deprotonation of Ugi adducts results in intermediate B. Cu(III) complex B undergo reductive elimination to deliver copper catalyst and monocyclic compounds C which then participates second deprotonation and oxidative addition process to afford Cu(III) intermediate E rapidly.…”
Section: Resultsmentioning
confidence: 86%
“…To our delight, better outcome was obtained by using DMSO as solvent and the desired product 5 a was delivered in 78% yield (Table 1, entry 7). Other bases, such as tBuONa, NaH, NaOH, Cs 2 CO 3 , K 2 CO 3 were further screened and all delivered inferior results (Table 1, entries [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Vachhani and Van der Eycken reported a strategy to synthesize a broad scope of spiroindolinone‐isoindolinones by Buchwald–Hartwing addition elimination strategy starting from dihalo N‐substituted N ‐benzamides (Scheme 44). [98] A range of electron‐withdrawing and electron‐donating substituents on the substrates were compatible with these reaction conditions.…”
Section: Cross‐coupling: Annulation/cyclizationmentioning
confidence: 78%